The contribution of international jurisprudence in the development of general principles of International law - Djeridi, Zahra; Filali, Kamel (Journal of Human Sciences, 2020)
The general principles of law mentioned in article 38 of the Statute of the ICJ. play a structural role in the edification of the rules of public international law in order to be in phase with the strong acceleration of the level of international relations on the one hand, and to make up for the deficiten countered by international courts during the settlement of international disputes , on the other hand. The jurisprudence of the old CPJI and of the CIJ revealed a set of principles, which flowed from Internal, laws to general international law and this so that its rules are consistent with the rapid dynamics of its expansion at the horizontal level of its branches. With this, our study addresses the idea of ​​the development of international law under international jurisprudence.